Magnesium supplementation on children with severe protein energy malnutrition - Khalil, Md Ibrahim; Al-Baki, Abdullah; Akhter, Nasrin; Al-Azad, Md Abdus Samad; Zafreen, Farzana; Wahab, Md Abdul (Journal of Armed Forces Medical College, Bangladesh, 2009)
doi:10.3329/jafmc.v4i2.1821 JAFMC Bangladesh Vol.4(2) 2008 10-13